No evidence of moral licensing in a laboratory bribe-taking task - Bahník, Štěpán; Vranka, Marek (Scientific reports, 2022)
Moral licensing posits that previous moral acts increase the probability of behaving immorally in the future. According to this perspective, rejecting bribes, even because they are too small, would create a kind of "license" for taking (presumably larger) bribes in the future. On the other hand, the desire for consistency in behavior predicts that previous rejection of bribes will increase the probability of rejection for bribes offered in the future. Using a laboratory task modeling the decision to take a bribe, we examined how resisting and succumbing to the temptation to take a bribe affects later bribe-taking. Participants (N = 297) were offered either low bribes first and high bribes later or vice versa. Low bribes were in general rejected more often and the results showed some weak, nonsignificant evidence that bribe-taking may be influenced by the order of the sizes of offered bribes. However, there was no evidence of an increased probability of taking bribes after being offered the low bribes first and thus no evidence in support of the moral licensing effect.
Keywords: mravy; Morals; Humans; motivace; Motivation; lidé